مقارنة بعض طرائق التعويض الأحادي للبيانات المفقودة لدالة الكثافة الاحتمالية للتوزيع الطبيعي ثنائي المتغيرات - عباس تهاني مهدي; محمد محمد جاسم; نايف قتيبة نبيل (Journal of Economics and Administrative Sciences, 2010)
In this paper we suggest new method to estimate the missing data in bivariate normal distribution and compare it with Single Imputation method (Unconditional mean and Conditional mean) by using simulation.